Enhancing Instructional Quality in Macro-Unit Physical Education Pathways Informed by Nonlinear Pedagogy - Chen, Cong; Hu, Yangyan (Quality in Sport, 2025)
The Physical Education and Health Curriculum Standards for Compulsory Education (2022 Edition) emphasize that diversified teaching approaches play an essential role in guiding students to think independently and engage in self-directed practice, thereby fostering their comprehensive practical competence and innovative awareness. Accordingly, traditional single-mode instruction, in which teachers demonstrate and students imitate, must be transformed. Against this backdrop, the present study employs the methods of literature review, experimental research, and logical analysis to investigate the application paradigm of ecological dynamics theory in physical education. The primary manifestation of ecological dynamics in this field is nonlinear pedagogy. The findings indicate that nonlinear pedagogy, through a constraint-led mechanism (the triadic constraints of individual–environment–task), effectively addresses the common dilemmas in teaching—namely, weak student interest, disconnection between learning contexts and skill application, and overly lengthy instructional tasks—by focusing on three dimensions: constructing high-quality learning situations, reinforcing task degeneracy, and stimulating students’ self-organization. Based on these findings, the application of this teaching approach contributes to enhancing students’ exploratory engagement and capacity for self-organization, promotes positive transfer of motor skills, and provides both theoretical support and practical reference for the optimization of large-unit teaching models in physical education.